2015
DOI: 10.1016/j.molmet.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

SOCS3 deficiency in leptin receptor-expressing cells mitigates the development of pregnancy-induced metabolic changes

Abstract: ObjectiveDuring pregnancy, women normally increase their food intake and body fat mass, and exhibit insulin resistance. However, an increasing number of women are developing metabolic imbalances during pregnancy, including excessive gestational weight gain and gestational diabetes mellitus. Despite the negative health impacts of pregnancy-induced metabolic imbalances, their molecular causes remain unclear. Therefore, the present study investigated the molecular mechanisms responsible for orchestrating the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 44 publications
2
46
0
4
Order By: Relevance
“…In mice exposed to high-fat diets, increased hypothalamic expression of SOCS3 decreases leptin sensitivity, increases the food intake and favors the development of diet-induced obesity (Briancon et al, 2010; Mori et al, 2004; Pedroso et al, 2014). In addition, our group recently showed that SOCS3 deficiency in leptin receptor-expressing cells blunts the increased food intake typically observed during pregnancy and lactation (Zampieri et al, 2015). Since leptin inhibits food intake in part by reducing the activity of NPY/AgRP neurons (Morton et al, 2014), the reduced hypothalamic SOCS3 expression may have favored the anorexigenic effects of leptin during lactation resulting in lower expression of NPY and AgRP which, in turn, led to the decreased food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In mice exposed to high-fat diets, increased hypothalamic expression of SOCS3 decreases leptin sensitivity, increases the food intake and favors the development of diet-induced obesity (Briancon et al, 2010; Mori et al, 2004; Pedroso et al, 2014). In addition, our group recently showed that SOCS3 deficiency in leptin receptor-expressing cells blunts the increased food intake typically observed during pregnancy and lactation (Zampieri et al, 2015). Since leptin inhibits food intake in part by reducing the activity of NPY/AgRP neurons (Morton et al, 2014), the reduced hypothalamic SOCS3 expression may have favored the anorexigenic effects of leptin during lactation resulting in lower expression of NPY and AgRP which, in turn, led to the decreased food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several populations of leptin receptorexpressing neurons in mice are directly responsive to prolactin (37). Furthermore, inactivation of the Socs3 gene in leptin receptor-expressing cells improves leptin sensitivity in pregnant mice and mitigates major gestational metabolic adaptions (38). Altogether, these findings suggest that changes in prolactin levels during pregnancy lead to leptin resistance, which, in turn, is responsible for orchestrating many metabolic adaptations commonly observed in pregnant animals.…”
Section: The Hypothalamus As a Target Of Prolactin To Modulate Severamentioning
confidence: 95%
“…Leptin-responsive neurons were determined by assessing cells that expressed pSTAT3 after an acute leptin stimulus, as previously described (Donato Jr. et al, 2010;Nagaishi et al, 2014;Zampieri et al, 2015). Mice were fasted for 5 h and received a subcutaneous injection of mouse recombinant leptin (5 µg/g).…”
Section: Experimental Procedures 421 Evaluation Of the Proportion Omentioning
confidence: 99%